AB0731 Investigation of Regulatory T Cells in Systemic Sclerosis. (9th June 2015) - Ugor, E.; Simon, D.; Pap, R.; Németh, P.; Minier, T.; Czirják, L.; Berki, T.
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune disease affecting multiple organs. It is characterized by excessive extracellular matrix deposition in the skin and internal organs accompanied by vascular damage and alterations of immune function. Regulatory T cells take part in the regulation of the immune system, development of tolerance against self antigens and the inhibition of autoimmunity. The role of Tregs seem to be essential in the pathogenesis of SSc. Objectives: The aim of our work was to study the changes in the ratio of Treg populations and their cytokine production in peripheral blood samples of SSc patients compared to healthy controls (HC) and to evaluate the changes in relation to the activity and severity of the disease. Methods: Peripheral blood samples were collected from SSc patients regularly visiting the Department of Rheumatology and Immunology not on immunosuppressive therapy and from HCs. PBMCs were isolated using ficoll gradient centrifugation and stimulated with the combination of PMA/ionomycin/brefeldin. Tregs (CD4+CD25+Foxp3+CD127-), Treg subgroups based on CD62L positivity and their cytokine production (IL-10, TGFβ) were investigated using flow cytometry. Results: The ratio of Treg cells was increased in SSc compared to HCs while percentage of the IL-10 producing Tregs was lower. The ratio of CD62L+ Treg cells was higher in SSc than in HCs and their TGFβ producing proportion was decreased. The percentage of the IL-10 producing CD62L+ Treg cells was lower in active SSc compared to the inactive group. Conclusions: According to our results the alterations of the ratio of Treg populations and their cytokine producing proportion in SSc patients is different from HCs and correlates with the activity of the disease. Consequently our study can help the early diagnostics of SSc and the assessment of its activity. Disclosure of Interest: None declared